Estudo da transferência de calor e de massa em um leito fixo espesso de grãos de sorgo com reversão de sentido do escoamento de ar - Barbosa, Luan da Silva (Universidade Federal de São Carlos, 2022)
Drying is one of the highest cost unit operations in the chemical industry, with complex momentum, heat and mass transfer mechanisms. The main objective of this work was to develop a systematic study on thick layer drying, focusing on specific and particular aspects of the sorghum grain, in addition to improving the instrumentation and operation of the data acquisition unit. Sorghum grains were pre-humidified before being placed into the fixed bed. Temperature and moisture measurements were taken over time for different axial positions during drying with and without reversal of the air flow direction at operating temperatures of 50 and 60°C and air velocity of 2,1 m∙s-1. The reversal started at the initial time of 10 min with a change in the air flow direction every 30 min. Reverse drying effectively decreased temperature and moisture gradients along the axial positions compared to conventional drying with upward airflow. Both thermal and mass experiments demonstrated that the drying of sorghum is controlled entirely by diffusion, being a slower process than the drying of inorganic materials. Previous thin layer essays at 40, 50 and 60°C and air velocity of 2,1 m∙s-1 showed that drying had the two phases of decreasing rates usual in diffusion-controlled processes. In fact, both heat and mass transfer measurements showed that the drying of sorghum was entirely diffusion controlled, being a slower process than the drying of inorganic materials. The kinetic models that best fit the thin layer drying data at the three temperatures were the Page and Overhults models, with R² of 0.999. A comparison was made between the drying, in a fixed bed and thick layer, of sorghum with that of alumina and barley. The similarity of the moisture and temperature profiles between sorghum and barley was observed, as they are both organic materials, as well as greater gradients remain at the end of barley drying due to its irregular shape, 4 times larger size and lower thermal conductivity when compared to drying sorghum. Comparing the drying of sorghum with the drying of alumina, it was possible to verify the difficulty that this material presents in order to represent a grain well, because, despite not shrinking (an ideal characteristic), it undergoes the re-wetting process when the reversion of air flow is applied, since half of the drying time is controlled by the convective mechanism.
Study of heat and mass transfer in a thick fixed bed of sorghum grains with reversal of the air flow direction
Keywords: Secagem; Leito fixo; Reversão; Sorgo; Mecanismo difusivo; Mecanismo convectivo; Drying; Fixed bed; Reversal; Sorghum; Diffusive mechanism; Convective mechanism; ENGENHARIAS::ENGENHARIA QUIMICA